CFTR is required for the migration of primordial germ cells during zebrafish early embryogenesis. Issue 3 (September 2018) - Liao, Huijuan; Chen, Yan; Li, Yulong; Xue, Shaolong; Liu, Mingfeng; Lin, Ziyuan; Liu, Yanyan; Chan, Hsiao Chang; Zhang, Xiaohu; Sun, Huaqin
Abstract : Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene affect fertility in both sexes. However, the involvement of CFTR in regulating germ cell development remains largely unknown. Here, we used zebrafish model to investigate the role of CFTR in primordial germ cells (PGCs) development. We generated a cftr frameshift mutant zebrafish line using CRISPR/Cas9 technique and investigated the migration of PGCs during early embryo development. Our results showed that loss of Cftr impairs the migration of PGCs from dome stages onward. The migration of PGCs was also perturbed by treatment of CFTRinh-172, a gating-speciﬁc CFTR channel inhibitor. Moreover, defected PGCs migration in cftr mutant embryos can be partially rescued by injection of WT but not other channel-defective mutant cftr mRNAs. Finally, we observed the elevation of cxcr4b, cxcl12a, rgs14a and ca15b, key factors involved in zebrafish PGCs migration, in cftr- mutant zebrafish embryos. Taken together, the present study revealed an important role of CFTR acting as an ion channel in regulating PGCs migration during early embryogenesis. Defect of which may impair germ cell development through elevation of key factors involved in cell motility and response to chemotactic gradient in PGCs.